The influence of artificial intelligence on critical thinking ability in mathematics: A systematic literature review - Arifin, M Zainul; Zulkarnain, Iskandar; Ansori, Hidayah (Universitas Islam Negeri Raden Intan Lampung, 2025)
Artificial intelligence (AI) is rapidly expanding in mathematics education; however, its impact on students' critical thinking skills remains not fully understood. As AI integration in learning increases, evaluating how this technology influences students' cognitive abilities is essential. This study aims to explore the impact of AI on critical thinking skills in mathematics learning through a Systematic Literature Review. Following the PRISMA protocol, the Systematic Literature Review (SLR) approach was used to collect and analyze relevant studies. The reviewed studies consisted of Scopus-indexed articles published in the last ten years, resulting in eight articles selected for further analysis. The findings indicate that AI use can positively contribute to students' critical thinking development, particularly in supporting interactive learning. However, there are also negative effects when students become overly reliant on technology, leading them to solve problems procedurally without a deep conceptual understanding. This study concludes that AI can effectively enhance students' critical thinking skills in mathematics, provided it is implemented with appropriate strategies. The findings have implications for developing hybrid learning models that integrate AI with traditional teaching approaches to achieve optimal learning outcomes.